Nanocarrier anticancer drug-conjugates cause higher cellular deformations: culpable for mischief. (17th September 2020) - Kale, Narendra; Nandi, Semonti; Patil, Ashwini; Patil, Yuvraj; Banerjee, Shashwat; Khandare, Jayant
Abstract : Here we report nanocarrier–anticancer drug conjugates culpable of cellular deformations, critically evidenced through image-based analysis as a measure of karyoplasmic ratio (KR) and nuclear surface area (NSA). Abstract : Here we report nanocarrier–anticancer drug conjugates culpable for cellular deformations, critically evidenced through image-based analysis as a measure of karyoplasmic ratio (KR) and nuclear surface area (NSA). Multiwalled carbon nanotubes (MWCNTs) were coordinated additionally with Fe3 O4 nanoparticles (NPs) to evaluate the symbiotic influence, and further conjugated to Dox for evaluating the cellular kinetics and for measuring cell deformations. Cellular entry kinetics of the CNT (CNT–Dox and CNT–Cys–Fe3 O4 –Dox) nanocarriers and their efficiency in nuclear localization were evaluated using cervical cancer (HeLa) cells. Of note, the Dox-bound nanocarriers showed significantly enhanced cell toxicity over the free form of the drug. CNT–Dox and CNT–Cys–Fe3 O4 –Dox influx occurred within 4 hours, while maximum cellular retention of Dox was observed for CNT–Dox at 24 h. However, the highest KR (∼0.51) was observed for CNT–Dox within 8 hours indicating similar cellular deformations using nanocarrier anticancer drug-conjugates to that of free Dox (KR ∼0.50) at 4 hours. In addition, we observed increased NSA at 4 h in Dox treatment whereas in the case of the Dox conjugated nanocarrier, increased NSA was noted at 8 h treatment. At 8 h exposure of HeLa cells with Dox conjugates, we observed that the cells fall into distinct regions of the morphospace with respect to KR and NSA. Conclusively, nano delivery systems considered for clinical and biomedical translations must take into account the possible negative influences imparting higher cellular deformations and secondary adverse effects over the free form of the drug.